Influence of competition day on cognitive control and HRV in young male gymnasts - Sartor, F.; Capuzzoni, S.; Rospo, G.; La Torre, A.; Vailati, F.; Vailati, E. (The Journal of Strength and Conditioning Research, 2017)
In gymnastics, high levels of executive attention and physical and coordinative capacities are required. However, training planning does not usually account for dynamic alterations in cognitive capacity. This study investigated whether cognitive capacity was altered by the approach of a competition. Ten elite male gymnasts (16 ± 2 years, 57.3 ± 16.1 kg, 1.64 ± 1.27 m) were monitored for sleep, life demands, rating of perceived exertion (RPE), and pain, starting 5 days before the competition and up to 5 days after it. Stroop task performance and concomitant heart rate variability (HRV) were monitored 5 days and 1 day before the competition and then 1 and 5 days after. Sleep and life demands were not affected by the competition. Localized pain ranged from mild to moderate levels throughout the observation period. It weakly correlated with RPE (r = 0.241, p = 0.010) and moderately with number of errors (NoEs) (r = 0.639, p = 0.047). The RPE was higher for the competition day (p = 0.002). Median reaction times during the Stroop task were higher in the period preceding the competition (p < 0.001) for similar NoEs. The HRV during the congruent stimuli task showed higher root mean square differences of successive beats, portion of normal to normal intervals exceeding 50 milliseconds, and high frequency after the competition (p = 0.05). Poincare plot SD2 showed a positive correlation with Stroop task NoEs (r = 0.590, p < 0.001). In conclusion, the period preceding an important competition affected cognitive performance and HRV in young male gymnasts. A practical implication of this study is that training loads could be adjusted according to mental stress before a competition.